Experimental investigation on the use of steel-concrete bond tests for estimating axial compressive strength of concrete: part 1 - Silva, B. V. (2013)
This study analyzes the feasibility of using steel-concrete bond tests for determining the compressive strength of concrete in order to use it as a complement in the quality control of reinforced concrete. Lorrain and Barbosa (2008) 14] and Lorrain et al. (2011) 15] justify the use of a modified bond test, termed APULOT, to estimate the compressive strength of concrete, hence increasing the possibilities for the technological control of reinforced concrete for constructions. They propose an adaptation of the traditional pull-out test (POT) method, standardized by the CEB / FIP RC6: 1983 8], because it is a low complexity and low cost test. To enable the use of the APULOT test as a technological control test of concrete at construction sites requires determining its methodology and adapting the experimental laboratory practice to the construction itself. The aim of this study is to evaluate the possibility of conducting compressive strength estimates using bond stress data obtained by the traditional pull-out tests (POT). Thus, two concrete compositions of different classes were tested at 3, 7 and 28 days. Ribbed bar specimens (nominal diameters of 8, 10 and 12.5 mm) were also used in the preparation stage, totaling 108 POT tests. The results show that the correlation between the maximum bond stress and the compressive strength of concrete is satisfactory in predetermined cases, at all ages tested, reinforcing the purpose of consolidating this test as a complementary alternative to control the quality of reinforced concrete. In the second part of this paper the test results obtained with the APULOT method are presented and discussed.